The Impact of Lagging-Region Status on District Poverty in Indonesia - Nasrudin, Rus'an (Economics and Finance in Indonesia, 2016)
Reducing subnational imbalances of development progress is unquestionable policy for heterogeneous Indonesia. This paper examines the impact of policy that assigns a lagging-region status namely status daerah tertinggal (DT) on poverty rate and poverty gap among districts in Indonesia in the two period of SBY presidency. The panel data fixed effect combined with propensity score matching is used to tackle the selection bias due to the nature of the policy, unobserved heterogeneity and omitted variable bias. The results show that the lagging-region status that was aimed to mainstream central and district's budget toward lagging regions statistically significant reduces poverty rate and poverty gap in the period. The DT status, on average is associated with 0.75 percentage point of reduction in the poverty rate and 7% reduction in the poverty gap index.